The influence of intrinsic water permeation on different dentin bonded interfaces formation. (May 2016) - Sartori, Neimar; Peruchi, Lais Dalmagro; Phark, Jin-Ho; Duarte, Sillas
Abstract: Objectives: To determine the effects of intrinsic wetness on the formation of dentin bonding interfaces of four resin cement systems bonded to dentin under different pulpal pressures. Methods: Thirty-six freshly extracted third molars were selected and processed for dentin μTBS. The teeth were randomly assigned into 12 experimental groups, according to the adhesive luting system [Adper Single Bond Plus (3 M ESPE) combined with two luting agents RelyX ARC (3 M ESPE) and heated Filtek Z250 Universal Restorative (3 M ESPE), Clearfil CD Bond (Kuraray) combined with Clearfil Esthetic Cement (Kuraray), and RelyX Unicem 2 Automix (3 M ESPE)] and pulpal pressure (0, 5, and 20 cm of simulated pulpal pressure). Leucite-reinforced glass-ceramic slabs (IPS Empress CAD, Ivoclar Vivadent) of 3 mm thickness were bonded to dentin. The samples were stored in distilled water for 24 h and then sectioned in X/Y directions across the adhesive interface to obtain specimens with a cross section of 0.8 ± 0.2 mm 2 . All sticks were fractured by tension at a crosshead speed of 1.0 mm/min and the data were submitted to Kruskal-Wallis and Mann-Whitney Tests (α=0.05). Ultrastructural analysis of the interfaces was performed using Confocal Laser Scanning Microscopy (CLSM) and Scanning Electron Microscopy (SEM). Results: The statistical analyses showed that pulpal pressure decreased μTBS for all groups. Significantly higher μTBS values were obtained in heated Z250 group restored without any pulpal pressure. CLSM showed that the uptake of water through the dentin tubuli and their anastomosis of lateral branches during the adhesive luting procedures prevented adequate formation of the dentin bonding interfaces. SEM showed that the luting film created is material- dependent and all adhesive failure occurred at the resin-dentin interface. Conclusion: The constant intrinsic wetness replenishment prevents adequate formation of the hybrid layer. Clinical significance: Intrinsic moisture during adhesive luting procedures significantly affects the interaction between luting materials and dentin subtract and decreases the quality and bonding strength of the resin-dentin bond.